Identifikasi Jenis Ikan Kerapu dan Kakap Hasil Tangkapan Nelayan di Wilayah Perairan Provinsi Nusa Tenggara Barat - Santika, Lora; Anas, Azwar (Jurnal Ilmu Kelautan Lesser Sunda, 2024)
The West Nusa Tenggara Province (NTB) serves as a pilot location for the management of grouper and snapper fisheries, setting an example for other regions in Indonesia. The enactment of Regional Regulation (PERGUB) NTB No. 55 of 2023 has become a guide and reference for the Regional Government and other stakeholders in promoting sustainable management of grouper and snapper fisheries in the NTB Province. Economically, the production of grouper and snapper fisheries in the NTB Province ranks third and is one of the top ten contributors to national grouper and snapper fisheries production (KKP, 2013). Ecologically, grouper and snapper species play a crucial role as predators, balancing the composition of fish at lower trophic levels. This research aims to determine the composition of grouper and snapper species caught in the waters of the NTB Province. Data collection was carried out through monitoring the landing of catches at fish landing centers, spanning from the year 2016 to 2022. Based on the monitoring data, 68 species of grouper and 50 species of snapper were identified. Grouper species from the Epinephelidae family, including Epinephelus coioides, Plectropomus leopardus, Plectropomus maculatus, and Variola albimarginata, dominated the catches. Meanwhile, snapper species from the Lutjanidae family, such as Lutjanus malabaricus, Lutjanus argentimaculatus, Lutjanus gibbus, and Pristipomoides multidens, were prevalent. Eight types of fishing gear were identified for catching grouper and snapper, including bottom longlines, trolling lines, harpoons, handlines, drop lines, boat traps, fixed gillnets, and fish traps.